Association between C-reactive protein and normal tension glaucoma - Stojčić, Milan O; Hentova-Senćanić, Paraskeva; Babić, Dragan; Stojčić, Biljana; Stojković, Milenko; Žorić, Lepša (Vojnosanitetski pregled, 2017)
Background/Aim. C-reactive protein (CRP) is a systemic inflammatory marker associated with risk for cardiovascular disease (CVD). Some risk factors for CVD are associated with normal tension glaucoma (NTG), but the association between CRP and NTG has not been well defined yet. The aim of our study was to compare high-sensitivity CRP (hs-CRP) levels in plasma between patients with NTG and normal controls. Methods. We studied 20 patients (4 males and 16 females) with the NTG diagnosis and compared their CRP values to those obtained in 25 controls (5 males and 20 females) with no ocular disease. Both groups had similar demographic parameters (age, sex, body mass index – BMI) and similar vascular risk profile. Results. Plasma CRP levels were comparable between patients with NTG and controls (mean values 4.99 ± 0.77 mg/L, median 4.50 mg/L, range 2.50–18.90 mg/L and mean value 4.19 ± 0.30 mg/L, median 3.50 mg/L range 2.20–8.50 mg/L, respectively, p > 0.5. Conclusion. The results obtained in this study suggest that CRP levels are not altered in NTG patients.
Keywords: low tension glaucoma; c-reactive protein; atherosclerosis